Manhaj Muqtarah Li Ta’lîmi Mahârah Al-Kalâm Billughah Al-‘Arabiyyah Li Al-Hujjâj Al-Indûnîsiyyîn Fî Qâmûs Hiwâr Al-Hujjâj Wa Al-Mu’tamirîn - Hidayat, Rahmat; Kholiq Hasan, Moh. Abdul (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2024)
هدفت هذه الدراسة إلى تصميم المنهج المقترح في قاموس حوار الحجاج والمعتمرين، لغرض تسهيل معلمين قي تعليم مهارة الكلام باللغة العربية للحجاج الإندونيسيين. وهذا البحث يساعد المتعلم ومعلمي اللغة العربية على تعليم مهارة الكلام بشكل سريع ومناسب؛ بحيث ركّز المتعلمون (الحجاج) والمعلمون على التعليم والتعلم على مهارة واحدة فحسب، وهي مهارة الكلام. ويكون التعلم بحفظ المفردات والحوارات والتدريبات المتعلقة بالحج والمتعلقة بحياة الحجاج الإندونيسيين خلال مكوثهم في الدول العربية. ولإنجاز هذه الدراسة العلمية يسلك الباحث المنهج النوعي، وذلك من خلال تصميم المنهج المقترح من الكلمات المحتاجة والتعبيرات المحتاجة إليها لدى الحجاج، بالاعتماد على قاموس حوار الحجاج والمعتمرين وكتب تعليم اللغة العربية، والبحوث العلمية، والاستفادة منها في تعليم اللغة العربية للحجاج الإندونيسيين. أثبتت هذه الدراسة على أن بناء المنهج المناسب لتعليم مهارة الكلام للحجاج الإندونيسيين يتم بوضع الحوارات، والنصوص، وتُكْمِله التدريبات التي تختصُّ في فهم المسموع ومهارة الكلام المتعلقة بعملية الحجاج في المملكة العربية السعودية This study aimed to design the proposed curriculum in the dictionary of dialogue of pilgrims and Umrah performers, for the purpose of facilitating teachers in teaching speech skill in Arabic to Indonesian pilgrims. This research helps the learner and Arabic language teachers to teach the skill of speech quickly and appropriately, so that learners (pilgrims) and teachers focused on teaching and learning on only one skill, which is the skill of speech. Learning is done by memorizing vocabulary, dialogues and exercises related to Hajj and related to the lives of Indonesian pilgrims during their stay in Arab countries. To accomplish this scientific study, the researcher follows the qualitative approach, by designing the proposed curriculum from the needy words and expressions needed by pilgrims, relying on the dictionary of dialogue of pilgrims and Umrah performers, books on teaching the Arabic language, and scientific research, and benefiting from them in teaching Arabic to Indonesian pilgrims. The researcher continued to this study in the two results: First, there are several words of need in the dictionary of dialogue of pilgrims and Umrah performers, which are 276 words and expressions needed. Second, this study proved that building the appropriate curriculum for teaching speech skill to Indonesian pilgrims is done by developing dialogues and texts, and complemented by exercises that specialize in listening comprehension and speech skill related to the pilgrim process in the Kingdom of Saudi Arabia. This study proved that building the appropriate curriculum for teaching the skill of speech to Indonesian pilgrims is done by developing dialogues and texts, and complemented by exercises that specialize in hearing comprehension and speech skill related to the pilgrim process in the Kingdom of Saudi Arabia. Penelitian ini bertujuan untuk merancang kurikulum yang diusulkan dalam kamus dialog jamaah haji dan umrah, untuk tujuan memfasilitasi guru dalam mengajarkan keterampilan berbicara dalam bahasa Arab kepada jamaah Indonesia. Penelitian ini membantu peserta didik dan guru bahasa Arab untuk mengajarkan keterampilan berbicara dengan cepat dan tepat, sehingga peserta didik (jamaah) dan guru fokus pada pengajaran dan pembelajaran hanya pada satu keterampilan, yaitu keterampilan berbicara. Pembelajaran dilakukan dengan menghafal kosakata, dialog dan latihan yang berkaitan dengan haji dan terkait dengan kehidupan jamaah haji Indonesia selama mereka tinggal di negara-negara Arab. Untuk mencapai studi ilmiah ini, peneliti mengikuti pendekatan kualitatif, dengan merancang kurikulum yang diusulkan dari kata-kata dan ekspresi yang dibutuhkan oleh peziarah, mengandalkan kamus dialog peziarah dan pelaku umrah, buku-buku tentang pengajaran bahasa Arab, dan penelitian ilmiah, dan manfaat dari mereka dalam mengajar bahasa Arab kepada peziarah Indonesia.. Penelitian ini membuktikan bahwa membangun kurikulum yang tepat untuk mengajarkan keterampilan berbicara kepada peziarah Indonesia dilakukan dengan mengembangkan dialog dan teks, dan dilengkapi dengan latihan yang mengkhususkan diri pada pemahaman pendengaran dan keterampilan berbicara yang berkaitan dengan proses peziarah di Kerajaan Arab Saudi.